Long-acting HIV fusion inhibitor albuvirtide combined with ritonavir-boosted lopinavir for HIV-1-infected patients after failing the first-line antiretroviral therapy: 48-week randomized, controlled, phase 3 non-inferiority TALENT study. Issue 3 (September 2022) - Su, Bin; Yao, Cheng; Zhao, Qing-Xia; Cai, Wei-Ping; Wang, Min; Lu, Hong-Zhou; Mu, Ting-Ting; Chen, Yuan-Yuan; Liu, Li; Wang, Hui; He, Yun; Zheng, Yu-Huang; et al.
Highlights: Albuvirtide (ABT) is a novel long-acting HIV fusion inhibitor. ABT combined with LPV/r was non-inferior to LPV/r based three-drug regimen. ABT combined with LPV/r showed a good safety profile. ABT combined with LPV/r showed a trend of improvement in renal function. ABT might be an interesting alternative option for HIV treatment and prevention.